IN-DEPTH ANALYSIS OF THE INFLUENCE OF INTRINSIC MOTIVATION ON ACADEMIC ACHIEVEMENT AMONG HIGH SCHOOL STUDENTS: THE ROLE OF SOCIAL SUPPORT, LEARNING STYLES, AND SELF-PERCEPTION AS MEDIATORS - Muhammad Natsir (Adisam Publisher, 2023)
This research explores the interplay between intrinsic motivation and academic achievement among high school students, with a particular focus on the mediating roles of social support, learning styles, and self-perception. The study aims to gauge intrinsic motivation levels and unravel the intricate mechanisms influencing its impact on academic success through a mixed-methods approach, combining quantitative surveys and qualitative interviews. The anticipated findings seek to confirm a positive correlation between intrinsic motivation and academic achievement while providing nuanced insights into the mediating factors. Social support networks, diverse learning styles, and positive self- perception are examined as potential catalysts, adding depth to our understanding of the complex dynamics at play. The implications of these findings extend to actionable strategies for educators and policymakers to enhance evidence-based practices, fostering environments that not only propel academic success but also instill a lasting love for learning among high school students.